A Small-Molecule Inhibitor of RAD51 Reduces Homologous Recombination and Sensitizes Multiple Myeloma Cells to Doxorubicin - Alagpulinsa, David A.; Ayyadevara, Srinivas; Shmookler Reis, Robert Joseph (Frontiers in Oncology, 2014)
We previously reported high expression of RAD51 and increased homologous recombination (HR) rates in multiple myeloma (MM) cells, and showed that genomic instability and disease progression are commensurate with HR levels. Moreover, high RAD51 expression in vivo is associated with chemoresistance and poor patient survival. Doxorubicin (DOX) is one of the most widely used drug treatments in MM chemotherapy. DOX is cytotoxic because it induces DNA double-strand breaks, which can be repaired by RAD51-mediated HR; activation of this pathway thus contributes to resistance. To investigate the role of RAD51 in MM drug resistance, we assessed the ability of B02, a small-molecule inhibitor of RAD51, to enhance DOX sensitivity of MM cells. Combining low-toxicity doses of DOX and B02 resulted in significant synthetic lethality, observed as increased apoptosis and reduced viability compared to either agent alone, or to the product of their individual effects. In contrast, the combination did not produce significant synergy against normal human CD19+ B cells from peripheral blood. DOX induced RAD51 at both mRNA and protein levels, while arresting cells in S and G2. DOX treatment also increased the number of RAD51 foci, a marker of HR repair, so that the fraction of cells with ≥5 foci rose 4-fold, whereas γH2AX foci rose far less, implying that most new breaks are repaired. When B02 treatment preceded DOX exposure, the induction of RAD51 foci was severely blunted, whereas γH2AX foci rose significantly relative to basal levels or either agent alone. In MM cells carrying a chromosomally integrated reporter of HR repair, DOX increased HR events while B02 inhibition of RAD51 blocked the HR response. These studies demonstrate the crucial role of RAD51 in protecting MM cells from genotoxic agents such as DOX, and suggest that specific inhibition of RAD51 may be an effective means to block DNA repair in MM cells and thus to enhance the efficacy of chemotherapy.